Small cell lung cancer - news in the tumour´s biology - Pavlíčková, Klára; Matěj, Radoslav (Ceskoslovenska patologie, 2023)
Small cell lung carcinoma (SCLC) is a high grade neuroendocrinne tumour accounting for approximately 15 % of lung cancers. It is characterised by early relapse and low survival rate. The treatment has remained unchanged for decades. Histological and cytological characteristics are summarised in brief, along with genetic alterations of the tumour. A new molecular subtype classification is presented according to the expression of transciptional factors ASCL1 (SCLC-A), NEUROD1 (SCLC-D), POU2F3 (SCLC-P) and YAP1 (SCLC-Y). These subtypes represent different ways of tumorigenesis, and the distinct genomic alterations may offer new therapeutic strategies.
Keywords: transkripční faktory; small cell lung carcinoma– ASCL1; NEUROD1; POU2F3; Carcinogenesis; Humans; Small Cell Lung Carcinoma; Gene Expression Regulation, Neoplastic; YAP1; Transcription Factors; malobuněčný karcinom plic; karcinogeneze; small cell lung cancer; lidé; regulace genové exprese u nádorů